Deleuzian Intersections : Science, Technology and Anthropology - Jensen, Casper Bruun; Rødje, Kjetil (Berghahn Books, Inc., 2009)
Science and technology studies, cultural anthropology and cultural studies deal with the complex relations between material, symbolic, technical and political practices. In a Deleuzian approach these relations are seen as produced in heterogeneous assemblages, moving across distinctions such as the human and non-human or the material and ideal. This volume outlines a Deleuzian approach to analyzing science, culture and politics.